Cigarette Smoke-Induced Placental Adrenomedullin Expression and Trophoblast Cell Invasion - Kraus, Daniel M. (SAGE Publications, 2014)
Smoking in pregnancy reduces preeclampsia risk, but the mechanism of this effect is unknown. Prior studies have demonstrated that women with preeclampsia have lower placental adrenomedullin (AM) expression, and cigarette smoke extract (CSE) treatment of placental trophoblast cells in culture increases AM cellular production. We hypothesized that CSE alters trophoblast invasion through an AM-mediated mechanism, and that placental AM expression is greater among smokers. HTR-8/SVneo trophoblast cells were incubated for 24 hours in Matrigel-invasion chambers with 6 treatment groups: nonstimulated (NS), AM, AM inhibitor (AM(22-52)), 1% CSE, AM + AM(22-52), and 1% CSE + AM(22-52). Cells that penetrated the lower surface of the chambers were quantified, invasion indices were calculated, and compared using a 1-way analysis of variance with Bonferroni corrections for multiple comparisons. Trophoblast cells treated with both AM and 1% CSE demonstrated increased cellular invasion compared to NS controls (1.5-fold [P < .01] and 1.45-fold [P < .01], respectively). Cotreatment with the AM inhibitor significantly attenuated the increased invasion seen with both AM and CSE alone. Next, the placental tissue was obtained from 11 smokers and 11 nonsmokers at term and processed for immunohistochemistry (IHC) and real-time quantitative polymerase chain reaction (PCR) for AM. Placentas from smokers demonstrated more intense AM staining and increased AM gene (ADM) expression compared to placentas from nonsmokers (P = .004 for IHC, P = .022 for PCR). The CSE increases trophoblast cell invasion through an AM-mediated process, and placental AM expression is increased among term smokers compared to nonsmokers. These findings provide evidence that the AM pathway may play a role in the protection from preeclampsia seen in smokers.